The North water : a novel - McGuire, Ian (Henry Holt and Company, 2016)
The Volunteer, a nineteenth-century Yorkshire whaling ship, becomes the stage for a confrontation between brutal harpooner Henry Drax and ex-army surgeon Patrick Sumner, the ship's medic, during a violent, ill-fated voyage to the Arctic.